-(2x-3)-(2x-6)+5=-6(x-1)-(2x-7)+3

Simple and best practice solution for -(2x-3)-(2x-6)+5=-6(x-1)-(2x-7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x-3)-(2x-6)+5=-6(x-1)-(2x-7)+3 equation:


Simplifying
-1(2x + -3) + -1(2x + -6) + 5 = -6(x + -1) + -1(2x + -7) + 3

Reorder the terms:
-1(-3 + 2x) + -1(2x + -6) + 5 = -6(x + -1) + -1(2x + -7) + 3
(-3 * -1 + 2x * -1) + -1(2x + -6) + 5 = -6(x + -1) + -1(2x + -7) + 3
(3 + -2x) + -1(2x + -6) + 5 = -6(x + -1) + -1(2x + -7) + 3

Reorder the terms:
3 + -2x + -1(-6 + 2x) + 5 = -6(x + -1) + -1(2x + -7) + 3
3 + -2x + (-6 * -1 + 2x * -1) + 5 = -6(x + -1) + -1(2x + -7) + 3
3 + -2x + (6 + -2x) + 5 = -6(x + -1) + -1(2x + -7) + 3

Reorder the terms:
3 + 6 + 5 + -2x + -2x = -6(x + -1) + -1(2x + -7) + 3

Combine like terms: 3 + 6 = 9
9 + 5 + -2x + -2x = -6(x + -1) + -1(2x + -7) + 3

Combine like terms: 9 + 5 = 14
14 + -2x + -2x = -6(x + -1) + -1(2x + -7) + 3

Combine like terms: -2x + -2x = -4x
14 + -4x = -6(x + -1) + -1(2x + -7) + 3

Reorder the terms:
14 + -4x = -6(-1 + x) + -1(2x + -7) + 3
14 + -4x = (-1 * -6 + x * -6) + -1(2x + -7) + 3
14 + -4x = (6 + -6x) + -1(2x + -7) + 3

Reorder the terms:
14 + -4x = 6 + -6x + -1(-7 + 2x) + 3
14 + -4x = 6 + -6x + (-7 * -1 + 2x * -1) + 3
14 + -4x = 6 + -6x + (7 + -2x) + 3

Reorder the terms:
14 + -4x = 6 + 7 + 3 + -6x + -2x

Combine like terms: 6 + 7 = 13
14 + -4x = 13 + 3 + -6x + -2x

Combine like terms: 13 + 3 = 16
14 + -4x = 16 + -6x + -2x

Combine like terms: -6x + -2x = -8x
14 + -4x = 16 + -8x

Solving
14 + -4x = 16 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
14 + -4x + 8x = 16 + -8x + 8x

Combine like terms: -4x + 8x = 4x
14 + 4x = 16 + -8x + 8x

Combine like terms: -8x + 8x = 0
14 + 4x = 16 + 0
14 + 4x = 16

Add '-14' to each side of the equation.
14 + -14 + 4x = 16 + -14

Combine like terms: 14 + -14 = 0
0 + 4x = 16 + -14
4x = 16 + -14

Combine like terms: 16 + -14 = 2
4x = 2

Divide each side by '4'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| (3t^2+6t)+(-9t^2-5t+5)= | | x(920-2x)=A(x) | | 3x+10=-26-6x | | 13g=39 | | 25(x-1)=x+1 | | 920x-2x^2=0 | | (-6b^2-2b-1)+(-2b^2+4b)= | | 5(2x-9)+7= | | 5x+4(5x+3)= | | 12(y)=384 | | 1996+43x+7385-67x= | | -18n*18=9 | | 12x-13-6x+4= | | 9p-7=74 | | 18n*18=9 | | 4+42x=21x+16 | | 3k-11=5-k | | p=7k^2-14k+1 | | 18.7+k=32.2 | | -18nx=9 | | (-n^3-8n-6)+(-8n^3+9n)= | | 3x-7+5=-(4x+7)+17x | | 0.5r+3=6 | | 9x+2y=114 | | 0.5+3=6 | | c=4d+5 | | 4(a-11)-7(2a+1)=-2.28 | | Z+6.8=15 | | -4.8f+6.8=-8.48 | | 8=7-2(7x+2) | | 3-2x=1-3x | | x^2=10(10-x) |

Equations solver categories